USE OF CHINESE MEDICINE AMONG COLORECTAL CANCER PATIENTS: A NATIONWIDE POPULATION-BASED STUDY. - Tsai, Shiang-Jiun; Ruan, Ying-Xu; Lee, Chinh-Chih; Lee, Moon-Sing; Chiou, Wen-Yen; Lin, Hon-Yi; Hsu, Feng-Chun; Su, Yu-Chieh; Hsu, Ta-Wen; Hung, Shih-Kai (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Traditional Chinese medicine (CM) appears to be used worldwide, especially by cancer patients. The aim of the present study was to explore CM uses and CM non-users by patients with colorectal cancer (CRC).Materials and methods: A retrospective study was conducted using registration and claims data sets for 2007 from the National Health Insurance Research Database. Patients with colorectal cancer were identified from the Registry for Catastrophic illness Patients. Binary logistic regression was used to estimate odds ratios as the measure of association with the use of CM. Results: A total of 61,211 CRC patients diagnosed in 2007 were analysis. Most CM users preferred to visit private clinics (46.9%) with 306,599 visits. In contrast, the majority of CM non-users preferred to visit private hospitals (42.2%) with 538,769 visits. Among all 176,707 cancer-specific CM visit, there were 66.6% visits to CM outpatient department (OPD) of private hospitals, while in 477,612 non-cancer-specific CM visits, 62.0% was for private clinics. The proportion of expenses for diagnostic fees for CM user in CM visits was much less than that for WM visits and CM non-users (US$4.6 vs. 29.3 vs. 33.5). The average cost for CM user in CM was less than that for WM visits and CM non-users (US$6.3 vs. 25.9 vs. 30.3). Female patients, younger age, and patients not living in the northern region, with higher EC or more comorbidities were more likely to receive CM treatment.Conclusion: The prevalence and costs of insurance-covered CM among CRC patients were low. Further longer longitudinal study is needed to follow up this trend.